Eccentricity in anthropology: David H. Kelsey's anthropological formula as a way out of the substantive-relational imago Dei debate - Milford, Stephen R. (Princeton theological monographs series, 2019)
Back cover: Eccentricity in Anthropology brings into conversation a constructive, critical interpretation of David Kelsey's Eccentric Existence with a central--yet often overlooked--debate in theological anthropology: the substantive-relational imago Dei. Milford's work explores new insights into human identity and dignity. In particular he demonstrates the value of an alternate constructive of humanity in the image of God. This construction utilizes an interpretation of Kelsey's anthropological formula so as to describe human identity as part of the created order in terms of its myriad features, which are externally rooted. Eccentricity in Anthropology demonstrates that an alternate approach to this debate is possible, and that one can combine important aspects of both substantive and relational thinking. As such, Milford's work is an important contribution to studies in the doctrine of the imago Dei. Taking Eccentric Existence's invitation to act as a springboard for further debate seriously, it presents one possible fruitful use of Kelsey's work to address theological anthropological questions. In a very real sense, this book is both a discussion in systematic theology and at the same time a work in contemporary historical theology